Workplace precrastination: conceptualization and scale development - Guo, Jie; Cho, Inchul; Nifadkar, Sushil (Frontiers in Psychology, 2025)
Workplace precrastination is the phenomenon wherein individuals tend to rush task-related activities at work and complete them as soon as possible. Due to its prevalence in everyday life (e.g., answering emails quickly, finishing work rapidly), precrastination has received increasing media and scholarly attention. However, despite growing interest in the topic, no psychometrically sound measure exists to capture workplace precrastination in organizations. We define workplace precrastination as the tendency of employees to complete an official task sooner than the expected deadline. This tendency manifests in three distinct dimensions: (1) immediate start, (2) rapid progress, and (3) early completion. Using three samples and a multi-wave approach to data collection, we develop a new scale to measure workplace precrastination and test its construct validity. We also examine whether precrastination is conceptually and empirically distinct from procrastination. Our findings suggest that workplace precrastination is distinct from procrastination and that it contributes unique variance to several organizationally relevant behavioral and attitudinal constructs.